The potency of endophytic bacteria isolated from Ficus septica as phytoremediation promoting agent of Cr (VI) contaminated soil - Nita Shilfiani Rohmah Nita Shilfiani Rohmah; SUHARJONO; YOGA DWI JATMIKO; DIAN SISWANTO; IRFAN MUSTAFA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rohmah NS, Suharjono, Jatmiko YD, Siswanto D, Mustafa I. 2020. The potency of endophytic bacteria isolated from Ficus septica as phytoremediation promoting agent of Cr (VI) contaminated soil. Biodiversitas 21: 1920-1927. Endophytic bacteria tolerant of chromium have the potential to reduce Cr (VI) to Cr (III) and produce compounds that can improve plant survival in Cr (VI) contaminated soils. This study was performed to isolate and identify Cr (VI)-tolerant bacteria from the endosphere of Ficus septica Burm.F growing on the tannery waste contaminated soil, Screening of bacteria was carried out based on the level of Cr (VI) tolerance. High tolerant isolates were tested for their potential of Indole Acetic Acid (IAA) and exopolysaccharide (EPS) production, phosphate solubilizing, and the presence of chromate reductase (ChR) genes. The most potential bacterial isolate was identified based on 16S rDNA sequences. The results showed that three isolates (E3, E4, and E8) were tolerant of Cr (VI) up to 900 mg/L. E8 isolates produced the highest IAA production (20.05 ?g/mL), phosphate solubilization (127.78 ?g/mL), and EPS production (9,70 ?g/mL), and all isolates had the ChR gene. E8 isolate was found to be 100% identical to Enterobacter cloacae ATCC 13047.